Multiple trait dimensions mediate stress gradient effects on plant biomass allocation, with implications for coastal ecosystem services. (7th May 2020) - De Battisti, Davide; Fowler, Mike S.; Jenkins, Stuart R.; Skov, Martin W.; Bouma, Tjeerd J.; Neyland, Penelope J.; Griffin, John N.
Abstract: The plant economic spectrum (PES) predicts a suite of correlated traits in a continuum from resource conservation to rapid resource acquisition. In addition to competing for resources, plants need to cope with other environmental stresses to persist and reproduce. Yet, it is unclear how multiple strategies (i.e. traits uncorrelated with the PES) affect plant biomass allocation, hindering our ability to connect environmental gradients to ecosystem services. We examined intraspecific dimensionality of leaf and root traits in the salt marsh pioneer species Spartina anglica across salinity, redox and sand content gradients, and related them to above‐ground and below‐ground plant biomass—properties associated with wave attenuation and sediment stabilization in coastal marshes. Through principal component analysis, we did not find support for a single PES trait dimension (strategy), but instead identified four trait dimensions: (a) leaf economic spectrum (LES, leaf analogue of PES); (b) fine roots‐rhizomes; (c) coarse roots; and (d) salt extrusion. Structural equation modelling showed a shift towards the conservative side of the LES under increasing salinity, while redox had a positive influence on the coarse roots dimension. In turn, these trait dimensions were strongly associated with above‐ground and below‐ground biomass (BLW biomass) allocation. These results indicate that under high salinity, plants will adopt a conservative strategy and will invest more in BLW biomass. Yet, high sediment redox would still allow plants to invest in above‐ground biomass. Therefore, plants' trait‐mediated biomass allocation depends on the specific combination of abiotic factors experienced at the local scale. Synthesis . Our study highlights the importance of considering multiple ecological strategies for understanding the effect of the environment on plants. Abiotic stresses can influence multiple trait strategy‐dimensions, with consequences for ecosystem functioning. Abstract : Our focal saltmarsh grass expressed conservative leaf traits and invested more in below‐ground biomass under high salinity. Yet, it was still able to express a high proportion of coarse roots and produce greater above‐ground biomass under high redox. Therefore, our study highlights the importance of multiple trait dimensions in connecting the environment to plant biomass allocation and ultimately ecosystem functions. Sommario: Lo spettro economico delle piante (SEP) postula che i tratti funzionali delle piante si distribuiscano lungo un continuum dalla conservazione all'acquisizione delle risorse. Oltre a competere per le risorse, le piante devono anche resistere allo stress ambientale se vogliono sopravvivere e riprodursi. Ciónonostante, non é ancora chiaro come strategie multiple (i.e. tratti correlati con il SEP) influiscano sull'allocazione della biomassa nelle piante, riducendo la nostra capacitá di legare gli effetti dei gradienti ambientali sui servizi dell'ecosistema. Abbiamo esaminato la dimensionalitá nei tratti funzionali di radici e foglie a livello intraspecifico della pianta pioniera laguanare Spartina anglica lungo gradienti di salinitá, redox e sabbia, e l'abbiamo legata alla biomassa apo‐ ed ipogea che é associata alla capacitá di attenuazione delle onde e della stabilizzazione del sedimento nelle lagune costiere. Attraverso l'analisi dei componenti principali, non abbiamo trovato supporto per una singola strategia SEP, ma abbiamo identificato quattro strategie: (a) lo spettro economico delle foglie (SEL, analogo fogliare del SEP); (b) radici fini – rizomi; (c) radici grossolane; e (d) estrusione fogliare di sale. Modelli di equazioni strutturali hanno dimostrato uno spostamento verso il lato conservativo del SEL all'aumentare dello stress salino, mentre una riduzione dello stress redox ha positivamente influenzato la produzione di radici grossolane. Di conseguenza, a queste dimensioni nei tratti funzionali era fortemente associata all'allocazione apo‐ ed ipogea delle biomassa delle piante. Questi risultati indicano che all'aumentare della salinitá le piante adottano una strategia di conservazione delle risorse ed investono maggiormente nella porsione ipogea. Ciónonostante, se le medesime piante crescono in sedimenti con alto redox, allora esse sono in grado di investire biomassa anche nella porzione apogea. Quindi, l'allocazioni di biomassa mediata dai tratti funzionali dipende dalla specifica combinazione dei fattori ambientali che a cui la pianta é sottoposta a livello locale. Sintesi . Il nostro studi sottolinea l'importanza di considerare diverse strategie ecologiche per capire quali effetti l'ambiente ha sulle piante. Gli stress aboitici possono influenzare questa multi‐dimensionalitá dei tratti funzionali, con consequenze per il funzionamento degli ecosistemi.